2021
DOI: 10.3389/fncel.2021.710390
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between the Complement System and Infectious Agents – A Potential Mechanistic Link to Neurodegeneration and Dementia

Abstract: As part of the innate immune system, complement plays a critical role in the elimination of pathogens and mobilization of cellular immune responses. In the central nervous system (CNS), many complement proteins are locally produced and regulate nervous system development and physiological processes such as neural plasticity. However, aberrant complement activation has been implicated in neurodegeneration, including Alzheimer’s disease. There is a growing list of pathogens that have been shown to interact with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 252 publications
(352 reference statements)
0
19
0
1
Order By: Relevance
“…T. gondii and Plasmodium spp. are obligate intracellular protozoan parasites that can significantly lead to the dysfunction and injury in the brain due to the interactions between these protozoa and complement system ( Table 1 ) [ 51 ]. It seems that the overactivation or overexpression of host’s complement components by Plasmodium parasites (or even on the parasite surface) participates in cerebral malaria (CM) pathogenesis.…”
Section: Parasite’s Complement Regulatory and Evasion Moleculesmentioning
confidence: 99%
“…T. gondii and Plasmodium spp. are obligate intracellular protozoan parasites that can significantly lead to the dysfunction and injury in the brain due to the interactions between these protozoa and complement system ( Table 1 ) [ 51 ]. It seems that the overactivation or overexpression of host’s complement components by Plasmodium parasites (or even on the parasite surface) participates in cerebral malaria (CM) pathogenesis.…”
Section: Parasite’s Complement Regulatory and Evasion Moleculesmentioning
confidence: 99%
“…Mounting evidence has suggested the importance of EBV and HHV-6 infection in the pathogenesis of MS ( Stuve et al, 2004 ; Virtanen et al, 2011 ; Tzartos et al, 2012 ; Meier et al, 2021 ; Bjornevik et al, 2022 ). As reviewed by Shinjyo et al (2021) viral infections, including HIV, herpes viruses, measles, TMEV, WNV, Zika, among other infectious agents, can modulate the complement system in the CNS, and this interaction may be involved in neurodegeneration and dementia. Therefore, one can assume that complement activation may also be playing an important role in the pathogenic effects of viral infections in MS.…”
Section: Understanding the Role Of Early Complement Components And It...mentioning
confidence: 99%
“…Growing evidence suggests that insulin and leptin play significant physiological roles in cognition ( Paz-Filho et al, 2008 ; Morrison, 2009 ; Gray et al, 2014 ; Arnold et al, 2018 ), and these signaling pathways may be promising therapeutic targets to alleviate cognitive impairment accompanied by obesity and MetS ( Mejido et al, 2020 ). On the other hand, obesity, visceral adiposity in particular, is frequently associated with immune dysregulation and infection susceptibility ( Hamdy et al, 2006 ; Conde et al, 2010 ; Kumari et al, 2019 ; Obradovic et al, 2021 ), while infection increases the risk of neurodegeneration and dementia ( Heneka et al, 2020 ; Shinjyo et al, 2021 ), suggesting the link between MetS, infection, and cognitive impairment.…”
Section: Metabolic Disturbance and Cognitive Impairmentmentioning
confidence: 99%
“…Recently, it has been shown that Aβ, a hallmark of AD, is an antimicrobial peptide, part of innate immunity to protect the host from various infectious agents ( Soscia et al, 2010 ; Kumar et al, 2016 ; Gosztyla et al, 2018 ), suggesting the necessity to revisit the role of amyloid plaque formation in AD pathogenesis. Above mentioned neurotropic viruses, such as HSV-1, HSV-2 and CMV, certain bacterial species, including spirochetes and P. gingivalis , fungi (e.g., Candida albicans ), and neurotropic parasite (e.g., T. gondii ), may cause disruption of brain functions via chronic inflammation and immune dysregulation in the brain ( Sochocka et al, 2017 ; Shinjyo et al, 2021 ). The antimicrobial hypothesis for AD proposes that Aβ generation and amyloid plaque formation are not the major culprit in AD pathogenesis, but rather a defense against such infectious agents ( Moir et al, 2018 ; Iqbal et al, 2020 ; Fulop et al, 2021 ).…”
Section: Insulin and Leptin Mediating The Link Between Infection And Neurodegenerative Disordersmentioning
confidence: 99%